Association between the triglyceride-glucose index and a procoagulant state in coronary artery disease. (14th October 2021) - Kosuta, D; Novakovic, M; Bozic Mijovski, M; Fras, Z; Jug, B
Abstract: Background: Metabolic risk factors and a procoagulant state represent major drivers of atherothrombosis. In terms of metabolic risk factors, the triglyceride-glucose (TyG) index has recently emerged as a marker of metabolic syndrome and an independent predictor of cardiovascular outcomes in patients with coronary artery disease (CAD). In terms of a procoagulant state, previous research suggests that CAD is associated with increased coagulation and impaired fibrinolytic activity, which may contribute to atherothrombotic events. We hypothesized that metabolic risk, as determined by TyG index, may be an important driver of hemostatic derangements in patients with CAD. Purpose: We sought to establish a possible association between the overall hemostatic, coagulation and fibrinolytic potentials (OHP, OCP and OFP), and the TyG Index in patients with CAD. Methods: Consecutive patients after a recent myocardial infarction (within 90 days from inclusion) had fasting blood samples withdrawn. OHP, OCP and OFP were determined with a previously validated method, using thrombin and recombinant tissue-type plasminogen activator, by absorbance measurements at 405 nm in 1 minute intervals for 40 minutes. Areas under the curve were constructed for OHP and OCP with the obtained measurements, OFP was calculated as the difference between the two aforementioned areas: OFP = [(OHP – OCP) / OCP] x 100 (%). Baseline data, cardiovascular risk factor profile and standard laboratory tests were collected. TyG index was calculated using the previously validated formula: TyG index = ln [triglyceride (mg/dL) x glucose (mg/dL) / 2]. Proportions were compared using the chi-squared test, linear regression models were constructed for the multivariate analysis. Results: We included 117 patients (mean age 56±10 years, 20% women). Arterial hypertension was present in 86 (73.5%), diabetes mellitus in 10 (8.5%), dyslipidemia in 75 (64.1%), family history in 46 (39.3%) patients; 54 (46.2%) were active smokers (within 2 years). Median OHP was 8.0 (interquartile range [IQR] 2.9), OCP was 22.6 (IQR 6.2), OFP was 66.0 (IQR 11)%. The TyG index was a strong univariate predictor of OCP (Beta 2.26 [0.282–4.242] p=0.026), and retained its statistical significance after multivariate adjustment for sex, age and traditional risk factors (R 2 0.23; ANOVA for regression p<0.001; Beta 1.98 [0.13–3.84], p=0.036). Conclusion: The TyG index, a marker of metabolic syndrome, is an independent predictor of a procoagulant state in CAD, as determined by the OCP. Our findings suggests that the metabolic syndrome may be an important driver of atherothrombotic risk in patients with CAD. FUNDunding Acknowledgement: Type of funding sources: None.